2012
DOI: 10.1063/1.4773239
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution of synchrotron x-ray microtomography in high energy range: Effect of x-ray energy and sample-to-detector distance

Abstract: Spatial resolution of 3D images obtained by synchrotron X-ray microtomography technique is evaluated using cyclic bar patterns machined on a steel wire. Influences of X-ray energy and the sample-to-detector distance on spatial resolution were investigated. Relatively high X-ray energies of 33-78 keV are applied due to the low X-ray transmission of transition metals. Best spatial resolution of about 1.2 µm was observed at the sample-to-detector distance range of 20-110 mm and at the energy range of 68-78 keV. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…These profiles were fitted in Sigmoid function, and then the full width of half maximum (FWHM), which is one of index that represents spatial resolution, was produced from first derivative of the fitted Sigmoid function. 11,12) The obtained FWHM were 10.1 μm, 5.2 μm and 1.0 μm in sample-todetector distance of 2 mm, 20 mm and 65 mm, respectively. The theoretical spatial resolution 12) was obtained in the 65 mm sample-to-detector distance.…”
Section: Absorption Edge Subtraction Imagingmentioning
confidence: 87%
See 2 more Smart Citations
“…These profiles were fitted in Sigmoid function, and then the full width of half maximum (FWHM), which is one of index that represents spatial resolution, was produced from first derivative of the fitted Sigmoid function. 11,12) The obtained FWHM were 10.1 μm, 5.2 μm and 1.0 μm in sample-todetector distance of 2 mm, 20 mm and 65 mm, respectively. The theoretical spatial resolution 12) was obtained in the 65 mm sample-to-detector distance.…”
Section: Absorption Edge Subtraction Imagingmentioning
confidence: 87%
“…However, effect of scattering and diffraction on spatial resolution has been reported for imaging in steels. 11,12) Therefore, sample-to-detector distance may affect concentration brought by absorption edge subtraction imaging. Sample-to-detector distance was set 2, 20 and 65 mm, and then its effect was examined in this study.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in a relatively high X-ray energy range, preferential forward scattering occurs, 12,14) which results in a remarkably low signal-tonoise ratio and spatial resolution when the sample-to-detector distance is less than 50 mm. 12,14) On the other hand, the ring artefacts observed above a sample-to-detector distance of 50 mm are gradually annihilated in the long-distance images. This may be attributable to degradation in the spatial resolution.…”
Section: Observation Of Dp Structurementioning
confidence: 99%
“…14) However, most of these studies have focused on simple damage evolution behaviour in continuum solids. Two-dimensional observation of longitudinal sections has been supplementarily employed for identifying microvoid nucleation mechanisms.…”
Section: D Fracture Behaviours In Dual-phase Stainless Steelmentioning
confidence: 99%